IMPROVEMENT OF SPEAKING SKILLS USING THE SOCIODRAMA METHOD IN INDONESIAN LESSONS FOR GRADE V STUDENTS - Jupon, Rara Marselina; Hamid, Abdul (JLCEdu (Journal of Learning and Character Education), 2022)
The purpose of this study is to improve students' speaking skills through the application of the Sociodrama Method to grade V students of Sangun Ratu Elementary School.  This study used Classroom Action Research. The subjects of this study were grade V students of Sangun Ratu Elementary School which amounted to 31 students (18 female students and 13 male students). The object of this study is speech skills and the Sociodrama Method. This class action research is carried out through two cycles. From the results of the actions of cycle I to cycle II there is an increase in speaking skills in students. The data collection method uses interview sheets, observation sheets, documentation and evaluation tests as well as student worksheets. The data analysis technique used is that there are three stages, such as data reduction, data presentation (data exposure), and conclusion drawing (verification).   The result of this study is that the application of the Sociodrama Method can improve students' speaking skills.  This can be seen from the results of the research and supported by the following facts: (1) the accuracy of pronunciation (pronunciation) in cycle I is 78.6% and increases in cycle II, namely to 81.9%;  (2) fluency of speech in cycle I, which is 82% and increases in cycle II, which is to 83.2%;  (3) the courage of the opinion in cycle I was 38.6% and increased in cycle II, which was 72.2%. With the increase in the value of student speaking skills, it affects student learning outcomes, from 35.48% precyclical or 11 completed students increased to 53.33% or 16 students completed in cycle I, then increased again to 87.10% or 27 students completed in cycle II.  This study concluded that the application of the Sociodrama Method can improve speaking skills in grade V students of Sangun Ratu Elementary School for the 2020/2021 school year.